2015
DOI: 10.1002/dta.1843
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the composition of anabolic tablets using near infrared spectroscopy and Raman chemical imaging

Abstract: The use of performance enhancing drugs is a widespread phenomenon in professional and leisure sports. A spectroscopic study was carried out on anabolic tablets labelled as 5 mg methandienone tablets provided by police departments. The analytical approach was based on a two-step methodology: a fast analysis of tablets using near infrared (NIR) spectroscopy to assess sample homogeneity based on their global composition, followed by Raman chemical imaging of one sample per NIR profile to obtain information on sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 24 publications
(50 reference statements)
0
18
0
Order By: Relevance
“…The PC score surface image could manifest the trend of studied indicator or sample clustering. 3,30,31 But at other times, the score surfaces do not contain any chemical meaning and the method is inadaptable, especially when coping with compositional-complex chemical images.…”
Section: Principle Component Analysismentioning
confidence: 99%
“…The PC score surface image could manifest the trend of studied indicator or sample clustering. 3,30,31 But at other times, the score surfaces do not contain any chemical meaning and the method is inadaptable, especially when coping with compositional-complex chemical images.…”
Section: Principle Component Analysismentioning
confidence: 99%
“…17,20 PLS-DA is also based on the PCA decomposition, the difference being that the combinations of variables, called PLS factors or latent variables, are defined in such a way that the covariance of the instrumental data with the response variable (predefined classes) are maximized, leading to quantitative methods with low errors and high discrimination power between the different classes in discriminant analysis. 13,15,18,20 PLS-DA is performed using binary coding, in which a dummy discrete response vector y is attributed to the data set, such as 0 for counterfeit samples and 1 for original samples.…”
Section: Partial Least Squares -Discriminant Analysis (Pls-da)mentioning
confidence: 99%
“…17,20 PLS-DA is also based on the PCA decomposition, the difference being that the combinations of variables, called PLS factors or latent variables, are defined in such a way that the covariance of the instrumental data with the response variable (predefined classes) are maximized, leading to quantitative methods with low errors and high discrimination power between the different classes in discriminant analysis. 13,15,18,20 PLS-DA is performed using binary coding, in which a dummy discrete response vector y is attributed to the data set, such as 0 for counterfeit samples and 1 for original samples. 14,17,21,22 In the training stage, the method is trained to assign "membership values", one for each class; a test sample is then assigned to a specific class if its y value surpasses a specific prediction threshold that may be estimated by establishing confidence limits for each sample classified.…”
Section: Partial Least Squares -Discriminant Analysis (Pls-da)mentioning
confidence: 99%
See 1 more Smart Citation
“…Rebiere et al . showed that the two‐step implementation of near infrared (NIR) spectroscopy and Raman chemical imaging helped detect counterfeit tablets labelled as methandienone . Further studies of counterfeit products are offered by Custers et al .…”
mentioning
confidence: 99%